2007
DOI: 10.1091/mbc.e06-09-0813
|View full text |Cite
|
Sign up to set email alerts
|

An Essential Role for Talin during αMβ2-mediated Phagocytosis

Abstract: The cytoskeletal, actin-binding protein talin has been previously implicated in phagocytosis in Dictyostelium discoideum and mammalian phagocytes. However, its mechanism of action during internalization is not understood. Our data confirm that endogenous talin can occasionally be found at phagosomes forming around IgG-and C3bi-opsonized red blood cells in macrophages. Remarkably, talin knockdown specifically abrogates uptake through complement receptor 3 (CR3, CD11b/CD18, ␣ M ␤ 2 integrin) and not through the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
102
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 93 publications
(114 citation statements)
references
References 51 publications
12
102
0
Order By: Relevance
“…1D-F), talin RNAi induced concomitant decreases in the association and phagocytic indices (Fig. 1D,E), consistent with its crucial role in CR3 activation (Lim et al, 2007). RhoA RNAi, but not RNAi against RhoB or RhoC, strongly reduced the CR3-mediated percentage of phagocytosis (,50% decrease, Fig.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…1D-F), talin RNAi induced concomitant decreases in the association and phagocytic indices (Fig. 1D,E), consistent with its crucial role in CR3 activation (Lim et al, 2007). RhoA RNAi, but not RNAi against RhoB or RhoC, strongly reduced the CR3-mediated percentage of phagocytosis (,50% decrease, Fig.…”
Section: Resultssupporting
confidence: 74%
“…1A-C) (Lim et al, 2007). The largest reduction in FccR percentage phagocytosis was produced by RhoG RNAi (,50%, Fig.…”
Section: Resultsmentioning
confidence: 85%
“…Talin (but not vinculin) is also required for both F-actin and integrin accumulation at the immunological synapse (Nolz et al, 2007), and for the chemokine-induced increase in affinity of integrin VLA-4 (α4β1) for VCAM1, which is important in lymphocyte-endothelial cell adhesion (Manevich et al, 2007). In macrophages, talin 1 is required for phagocytosis that is mediated by αMβ2 integrin (complement receptor 3) (Lim et al, 2007), whereas a talin-PIPK1γ90 complex has been shown to play a novel role in clathrin-mediated endocytosis in the neuronal synapse (Morgan et al, 2004).…”
Section: Analysis Of Talin Function In Vertebratesmentioning
confidence: 99%
“…On the other hand, the association of the cytoplasmic b 2 tail with actin-binding proteins results in modification of the actin cytoskeleton and, hence, cell migration. Different consensus sequences of the b 2 cytoplasmic tail are known to associate with the actin-binding proteins talin [9], filamin [10], radixin [11] and a-actinin-1 [12], and also with the signaling proteins FAK [13], cytohesin 1 [14] and cytohesin 3 [15] that are the final effectors of inside-out signaling pathways.…”
Section: Introductionmentioning
confidence: 99%